MEMPERKUAT PAHAM MODERASI BERAGAMA DALAM MENANGKAL NARASI KEBENCIAN DI MEDIA SOSIAL - Hamam Burhanuddin; Fahmi Khumaini (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
The stigma of thoughts and movements to be radical and smells of violence still surrounds life in Indonesia, this is behind the importance of moderate Islamic thought by